2019
DOI: 10.1002/1873-3468.13627
|View full text |Cite
|
Sign up to set email alerts
|

Diverse roles for CDK‐associated activity during spermatogenesis

Abstract: The primary function of cyclin‐dependent kinases (CDKs) in complex with their activating cyclin partners is to promote mitotic division in somatic cells. This canonical cell cycle‐associated activity is also crucial for fertility as it allows the proliferation and differentiation of stem cells within the reproductive organs to generate meiotically competent cells. Intriguingly, several CDKs exhibit meiosis‐specific functions and are essential for the completion of the two reductional meiotic divisions required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 254 publications
(325 reference statements)
0
20
0
Order By: Relevance
“…CDK2 is a multifunctional kinase that is recognized to play multiple roles during germ cell development. These include regulating cell fate in spermatogonial stem cells [ 17 ], regulation of transcription in spermatocytes [ 18 ], and promoting homolog synapsis during meiotic prophase I ([ 10 ]; for reviews, also see [ 19 22 ]). During zygonema of meiotic prophase, CDK2 and its noncanonical activating partner Speedy A (see below) interact to promote stable interactions between telomeres and the inner nuclear envelope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDK2 is a multifunctional kinase that is recognized to play multiple roles during germ cell development. These include regulating cell fate in spermatogonial stem cells [ 17 ], regulation of transcription in spermatocytes [ 18 ], and promoting homolog synapsis during meiotic prophase I ([ 10 ]; for reviews, also see [ 19 22 ]). During zygonema of meiotic prophase, CDK2 and its noncanonical activating partner Speedy A (see below) interact to promote stable interactions between telomeres and the inner nuclear envelope.…”
Section: Introductionmentioning
confidence: 99%
“…During zygonema of meiotic prophase, CDK2 and its noncanonical activating partner Speedy A (see below) interact to promote stable interactions between telomeres and the inner nuclear envelope. This action is essential for the DSB-stimulated homology search process needed for pairing of homologous chromosomes ([ 23 25 ]; reviewed in [ 19 ]; see also [ 26 ]). Consequentially, Cdk2 −/− and Speedy A −/− meiocytes display extensive nonhomologous synapsis and arrest at an identical pachytene-like stage [ 10 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The kinase activity of CDK2 is important for meiosis and spermatogenesis (Liu et al, 2014;Wang et al, 2014;Chauhan et al, 2016;Palmer et al, 2019). It has been reported that CDK2 phosphorylates SUN1 (Viera et al, 2015;Mikolcevic et al, 2016), but the function of SUN1 phosphorylation by CDK2 is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CDK2 and its activators, SPDYA and Cyclin E, are required for the bouquet formation (Palmer et al, 2019). In the Cdk2, Spdya, and Cyclin E knockout mice, telomeres dissociate from the NE, indicating that the LINC-linker-shelterin connection is broken down, but where the disconnection occurs is unknown (Viera et al, 2015;Manterola et al, 2016;Tu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this mutant, unresolved class II recombination intermediates persist, leading to the formation of chromosome entanglements at metaphase I (Crismani et al, 2012). MUS81 has a well-described role in the resolution of Holliday junctions (Osman et al, 2003) and there is also support for CDKs having a role in CO maturation (Palmer et al, 2019).…”
Section: The Localisation Of Class I Co Markers Is Restored In a Doubmentioning
confidence: 98%